Validation of Endogenous Reference Genes for qPCR Quantification of Muscle Transcripts in Atlantic Cod Subjected to Different Photoperiod Regimes - Nagasawa, Kazue; Lazado, Carlo; Fernandes, Jorge M. O. (IntechOpen, 2012)
None